Psychometric evaluation of a unified Portuguese-language version of the Body Shape Questionnaire in female university students - Silva, Wanderson Roberto [UNESP] (2016)
The objectives of this study were to develop a unified Portuguese-language version, for use in Brazil and Portugal, of the Body Shape Questionnaire (BSQ) and to estimate its validity, reliability, and internal consistency in Brazilian and Portuguese female university students. Confirmatory factor analysis was performed using both original (34-item) and shortened (8-item) versions. The model's fit was assessed with chi(2)/df, CFI, NFI, and RMSEA. Concurrent and convergent validity were assessed. Reliability was estimated through internal consistency and composite reliability (alpha). Transnational invariance of the BSQ was tested using multi-group analysis. The original 32-item model was refined to present a better fit and adequate validity and reliability. The shortened model was stable in both independent samples and in transnational samples (Brazil and Portugal). The use of this unified version is recommended for the assessment of body shape concerns in both Brazilian and Portuguese college students.